Glycoprotein maturation and quality control in the endoplasmic reticulum - Hebert, Daniel (Henry Stewart Talks, 2007)
Protein maturation in the secretory pathway, ER glycoforms, The glyco-code of the ER, Calnexin and calreticulin, Cotranslational folding, Influenza hemagglutinin, Oxidation of HA, HA truncations, Type I membrane proteins, Disease states involving ER folding and quality control, Structural determinants that cause retention, ER retention signals, Calnexin binding cycle, GT or UDP glucose glycoprotein: glycosyltransferase, Degradation of misfolded proteins, Carbohydrate trimming, EDEM1 functions